Effect of moderate-intensity seated exercise on the management of metabolic outcomes in hypertensive individuals with or without exercise habits - Hiroto Honda; Makoto Igaki; Motoaki Komatsu; Shin-ichiro Tanaka (Elsevier, 2021)
Background: We aimed to evaluate the effect of moderate-intensity seated exercise on metabolic outcomes in hypertensive individuals with or without exercise habits. Methods: Forty-two hypertensive individuals volunteered for this study and were classified into 3 groups by their habits and place for moderate-intensity exercise prior to this study: NONE (<2 days/week or no exercise; n = 13), HOME (≥30 min/day and ≥2 days/week at home; n = 15), and GYM (≥30 min/day and ≥2 days/week at a hospital gym; n = 14). They performed their daily activities as usual and seated exercise (stepping and stepping with trunk rotation; a range of 11-13 on the Borg rating of perceived exertion scale) for at least 15 min/day and at least 3 days/week for 12 weeks. Results: Thirty-five participants (age: 67.7 ± 5.9 years) completed the study, and there was no difference among the 3 groups regarding weekly exercise. The homeostasis model assessment of insulin resistance (HOMA-IR) value in the NONE group was significantly higher than that in the GYM group at baseline (p < 0.05), but it decreased significantly after 12 weeks (from 2.2 ± 0.8 to 1.7 ± 0.7, p < 0.05). Changes in HOMA-IR in the NONE group after 12 weeks was greater than that in the HOME and GYM groups (both p < 0.01). The HOME and GYM groups showed no significant changes in any of the variables. Conclusion: Moderate-intensity seated exercise may be an effective strategy to improve insulin resistance in hypertensive individuals without exercise habits.